Learning Styles in Students from the School of Human Movement Sciences and Quality of Life, Universidad Nacional, Costa Rica - Jorge Salas-Cabrera (Revista Electronic@ Educare, 2014)
The purpose of this research was to determine the learning style of students majoring in the B.A. Programs in Physical Education, Sports and Recreation (BEFDR) and Physical Health Promotion (BPSF), and the Licentiate Degree in Sports Performance (LRD) at the School of Human Movement Sciences and Quality of Life.  A total of 204 students participated in the study by answering the Horney-Alonso questionnaire (CHAEA). In general, results show that students tend to have a reflective learning style: BEFDR and LRD (14.34 ± 2.92), and BPSF (14.48 ± 2.72). As a conclusion, it was determined that the trend towards reflective learning is characteristic of those who received behavioral methodologies during their school career. In addition, due to the practical emphasis of the Physical Education and Sports Performance programs, their students tend to be more active.